2006
DOI: 10.1159/000090570
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Ophthalmic Regional Blocks: Their Treatment and Prevention

Abstract: Complications following ophthalmic regional anaesthesia are rare but are reported during both needle (intraconal and extraconal blocks) and blunt cannula (sub-Tenon’s block) techniques. At present there is no perfect technique of ophthalmic regional anaesthesia. This article reports on the complications, treatment and prevention of commonly used ophthalmic regional blocks. Thorough knowledge of the measures required to deal with complications when they occur are of paramount importance for safe clinical practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 115 publications
(103 reference statements)
1
66
0
Order By: Relevance
“…7 Topical anaesthesia with local anaesthetic drops or gel Here, local anaesthetic eye drops or gel is applied to the surface of the eye for anaesthesia. Rectus muscles are therefore not affected; anaesthesia is never complete and there is no akinesia.…”
Section: Sub-tenon's Blockmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Topical anaesthesia with local anaesthetic drops or gel Here, local anaesthetic eye drops or gel is applied to the surface of the eye for anaesthesia. Rectus muscles are therefore not affected; anaesthesia is never complete and there is no akinesia.…”
Section: Sub-tenon's Blockmentioning
confidence: 99%
“…Eyes with an axial length of more than 26 mm are more prone to globe damage (perforation and penetration); the risk of damage to the globe and optic nerve is also greater when the globe is rotated during injection. 7 It is therefore safer to introduce a needle as far laterally as possible because, if it is introduced at the junction of the medial two-thirds and lateral one-third of the inferior orbital rim, the inferior rectus, the inferior oblique muscles and their nerves may be damaged. 14 Needle blocks are generally avoided in patients receiving anticoagulants and sub-Tenon's block; in such cases, topical anaesthesia is preferred.…”
Section: Assessment and Preparation Of Patients Before Loco-regional mentioning
confidence: 99%
See 1 more Smart Citation
“…With no evidence for intravascular injection, the lack of structural brain abnormalities, and the most striking feature on post mortem examination being severe triple vessel coronary artery disease, it was concluded that this was primarily cardiac in origin; however, the possibility of brainstem anaesthesia should also be considered. The use of sub-Tenon's block for cataract surgery is becoming increasingly popular in the UK and it is felt to be a safer alternative to other anaesthetic techniques, despite the lack of a randomised double-blind study to validate conclusions regarding its relative safety [1]. 'Brainstem anaesthesia' is a complex phenomenon which may result from local anaesthesia entering the central nervous system, and it is a recognised complication of ophthalmic regional blocks, with various postulated and debated mechanisms and variable presentation [2].…”
mentioning
confidence: 99%
“…The use of sub-Tenon's block for cataract surgery is becoming increasingly popular in the UK and it is felt to be a safer alternative to other anaesthetic techniques, despite the lack of a randomised double-blind study to validate conclusions regarding its relative safety [1]. 'Brainstem anaesthesia' is a complex phenomenon which may result from local anaesthesia entering the central nervous system, and it is a recognised complication of ophthalmic regional blocks, with various postulated and debated mechanisms and variable presentation [2].…”
mentioning
confidence: 99%